The role of credit in the uptake of improved dairy technologies in Ethiopia - Freeman, H.A.; Jabbar, M.A.; Ehui, Simeon K.; Gebreselassie, N. (1996)
In Ethiopia smallholder livestock producers have adopted components of improved dairy technologies but the intensity of adoption remains low. It is hypothesized that credit-related constraints limit the ability of many smallholder farmers to make investments in crossbred cows and/or to purchase complementary inputs associated with improved dairy technologies. This paper assesses how credit influences farmers' investment and their production decisions. Farmers are classified as credit constrained or non-credit-constrained. The results showed that credit has had little influence on variables such as input use or farmers' marketing decisions.